Third Harmonic Generation of Optical Vortices Using Holography‐Based Gold‐Fork Microstructure. Issue 4 (13th February 2014) - Li, Gui Xin; Chen, Shu Mei; Cai, Yuan; Zhang, Shuang; Cheah, Kok Wai
<x xml:space="preserve">Abstract</x> Light with orbital angular momentum has found novel applications in macro‐manipulation, quantum optics, and optical communication, etc. The generation of orbital angular momentum in nonlinear media, such as second harmonic generation and high harmonic generation, is demonstrated using an optical superlattice and a gas medium. Here, by combining a gold‐fork microstructure with a conjugated polymer thin film with strong nonlinearity, both second‐ and third‐order harmonic generation of vortex beams with orbital angular momentum are created. Compared to the previously reported medium to generate nonlinear optical vortex, this approach brings great advantages in device miniaturization and provides a promising strategy for realizing on‐chip nonlinear optical vortex devices.